Wheat gluten/montmorillonite biocomposites: Effect of pH on the mechanical properties and clay dispersion - E. Cortes-Trivino; I. Martinez (eXPRESS Polymer Letters, 2018)
The addition of inorganic fillers into a bioplastic could increase its mechanical properties, which will be influenced strongly by the type of the clay dispersion. In this work, we have used montmorillonite nanoclays (MMT) to prepare biocomposites by means of an extrusion process. We present herein the effect of the pH and the addition of montmorillonite nanoclays (MMT) on the barrier and mechanical properties of wheat gluten based bioplastics. The pH of the samples was modified by adding aqueous solution of a strong acid or base (H2SO4 and NaOH). Tensile, dynamic mechanical thermal analysis (DMTA), water absorption and X-ray tests were carried out to study the influence of the above-mentioned variables on the physicochemical properties and rheological behaviour of bioplastics and biocomposites obtained. Tensile results showed that both Young’s modulus and tensile strength are higher at unmodified pH. However, the addition of MMT to an alkaline biopolymer matrix produced remarkable improvements in the rheological and mechanical properties because of a high exfoliation of the nanoclay noticeable in X-ray results. To summarise, extrusion process and the use of nanoclays present an excellent opportunity to develop wheat gluten bioplastics able to replace conventional products.